2023
DOI: 10.1002/smll.202208277
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Integrating 2D Confinement and High Sodiophilicity toward SnO2/Ti3C2Tx Composites for High‐Performance Sodium‐Metal Anodes

Abstract: The metallic sodium (Na) is characterized by high theoretical specific capacity, low electrode potential and abundant resources, and its advantages manifests itself as a promising candidate anode of sodium metal batteries (SMBs). However, the vaporization during the plating/stripping or uncontrolled growth of sodium dendrites in sodium metal anodes (SMAs) has posed major challenges to its practical applications. To address this issue, here, the SnO2/Ti3C2Tx composite is rationally fabricated, in which sodiophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…As shown in Figure b, the binding energy peaks located at 281.5, 284.8, 286.7, and 289.2 eV correspond to C-Ti, C-C, C-O, and O-CO bonds, respectively . The O 1s spectrum in Figure c presents the peaks of 529.0, 530.5, and 532.1 eV, which are assigned to the Ti-O bond in TiO 2 , Sn-O bond in SnO 2 and C-Ti-(OH) x , respectively . The generation of TiO 2 is due to the oxidation of Ti 3 C 2 T x under solvothermal conditions .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As shown in Figure b, the binding energy peaks located at 281.5, 284.8, 286.7, and 289.2 eV correspond to C-Ti, C-C, C-O, and O-CO bonds, respectively . The O 1s spectrum in Figure c presents the peaks of 529.0, 530.5, and 532.1 eV, which are assigned to the Ti-O bond in TiO 2 , Sn-O bond in SnO 2 and C-Ti-(OH) x , respectively . The generation of TiO 2 is due to the oxidation of Ti 3 C 2 T x under solvothermal conditions .…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the peak located at 532.1 eV should be attributed to the -OH groups on Ti 3 C 2 T x . The HRXPS of Ti 2p shown in Figure d could be divided into four Gaussian peaks located at 455.1 eV (C-T 2p 3/2 ), 458.9 eV (C-Ti 2p 1/2 ), 457 eV (Ti-O 2p 3/2 ), and 464.6 eV (Ti-O 2p 1/2 ), respectively. Related studies have shown that the oxidation of Ti 3 C 2 T x can produce more Ti-O bonds on its surface and effectively reduce the defects of the prepared sensing material. Through structural simulation and energy level calculation, it is found that its properties change from metal to semiconductor with the increase of oxidation level …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…28,29 Meanwhile, most 3D skeletons are not sodiophilic, which will bring about a huge nucleation barrier and hardly achieve uniform Na nucleation and deposition behaviors. 30,31 Consequently, it is of great significance to develop 3D skeletons with excellent sodiophilicity and a stable anode/electrolyte interface, and thus simultaneously harvest satisfactory cycling stability under high current density and areal capacity. 17,32 It is well known that a Li-Sn alloy is favorable for suppressing dendrite growth and realizing dendrite-free Li deposition due to its low chemical reactivity and high lithiophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of transition-metal oxides (TMOs) have led to their consideration as prospective anode materials in LIBs/SIBs. Among the TMOs, molybdenum-based materials have diverse structural compositions and exceptional electrochemical properties, making them versatile for various applications. , In particular, molybdenum trioxide (MoO 3 ) has attracted attention as a promising candidate for addressing the issues associated with conventional anode materials in LIBs/SIBs. , The layered arrangement of MoO 3 , comprised of MoO 6 octahedra linked by shared oxygen atoms, endows it with notable theoretical capacity, impressive cycle stability, and affordability. MoO 3 has been crafted into various nanoscale shapes, including nanowires, nanobelts, , nanorods, hollow nanospheres, nanosheets, and thin films, utilizing diverse techniques like thermal evaporation, hydrothermal synthesis, and sol–gel synthesis.…”
Section: Introductionmentioning
confidence: 99%